Theoretical and practical directions for the turbogenerators creation, taking into account the electric power industry development - Shevchenko, V. V.; Shayda, V. P.; Pototsky, D. V. (BoScience Publisher, 2021)
The paper identifies the main tasks of ensuring the country's energy independence in terms of contemporary problems associated with environmental problems, population growth, and an increase in its energy activity. It has been established that nuclear power plants will be the main sources of electricity for a long time, therefore, it is important to improve turbogenerators (TG). The directions were established in which research should be carried out in order to eliminate the lag behind world firms in the field of turbogenerator engineering: increasing the power in unit of execution, reducing the TG mass and dimensions, replacing hydrogen cooling with air cooling.
Keywords: electric power industry; energy efficiency; environmental safety; forecasting the electric power industry development; turbogenerators; capacity increase